Hemi-Castaing ligamentoplasty for the surgical treatment of chronic lateral ankle instability in young athletes: our 7 years experience: Hemi-Castaing surgery for ankle instability - Sperati, Gianluca; Ceri, Lorenzo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: in this study we report our 7-years experience (from January 2011 to December 2017) of 35 patients with chronic lateral ankle instability treated with the Hemi-Castaing reconstruction procedure, all performed in our clinic. Methods: thirty-five patients (F12-M23; median age around 31 yrs, range 18-52 yrs). All patients used to practice amateur sports at competitive level. The procedures were performed in 19 cases on the right ankle whereas in 16 cases on the left ankle. The average follow-up was 54.2 months. Results: of the 35 patients included in our study, all of them were able to practice sport as the same level as before from 80 to 100 days after intervention. Optimal functional results were achieved in all patients and no further episodes of ankle sprain occurred. All patients rated their outcome as good/excellent. No intra-operative complications were observed, whereas we noticed a case of surgical wound dehiscence after surgery. The Hemi-Castaing procedure provided a high lateral ankle stability, with excellent clinical and functional results. In our study, no significant difference in evertor strength was found according to side, and there was no significant change in E/I ratio. Moreover, joint position sense was not impaired. Conclusion. According to us, this surgical technique is efficient and safe, providing remarkable outcomes in the treatment of chronic lateral ankle instability.